Morphometric variations of three species of harvested cephalopods found in northern sea of Aceh Province, Indonesia - ZAINAL ABIDIN MUCHLISIN; BATMI ZULKARNAINI; SYAHRUL PURNAWAN; ACHMAD MUHADJIER; NUR FADLI; SAMANTHA H. CHENG (Society for Indonesian Biodiversity, 2014)
Muchlisin ZA, Zulkarnaini B, Purnawan S, Muhadjier A, Fadli N, Cheng SH. 2014. Morphometric variations of three species of harvested cephalopods found in northern sea of Aceh Province, Indonesia. Biodiversitas 15: 142-146. The purpose of the present studywas to evaluate the morphometrics of three harvested cephalopods, Sepioteuthis lessoniana, Sepia officinalis and Uroteuthis sp. found innorthern sea of Aceh Province, Indonesia. Sampling was conducted for six months from July to December 2012 in one week interval. Atotal of 318 cephalopods; 139 Sepioteuthis lessoniana, 139 Uroteuthis sp. and 40 Sepia officinalis were analyzed for morphometricstudy and 13 anatomical characters were measured to the nearest 0.01 mm using a digital caliper. Morphometric measurements weresignificantly different between the different species of cephalopods (ANOVA, p<0.05). S. officinalis differed in six morphologicalcharacters (head length, head width, tentacles length, gladius width, rancis width and length) from the squid species. Fin width andlength were significantly greater in S. lessoniana than in S. officinalis and Uroteuthis sp. On the other hand, Uroteuthis sp. hadsignificantly greater mantle lengths, standard lengths and gladius lengths than the other two cephalopod species (Duncan Test, p<0.05).However, fin width was similar between S. lessoniana and Uroteuthis sp., while eye diameter was similar between S. officinalis andUroteuthis sp. A Discriminant Function Analysis scatter plot successfully discriminated the three species indicating significantdifferences in morphological variation. This analysis also indicates that morphometrically, S. lessoniana and S. officinalis are moresimilar to each other despite being in different orders.